Assessment of Self-medication Practices in Urban and Rural areas of Kalaburagi, Karnataka - Biradar, SS; Marla, Sushruta; K, Chaitanya; S, Himaja; M, Chandini (Journal of Pharmacy Practice and Community Medicine)
Background: Self-medication can be defined as the use of drugs to treat self-diagnosed disorders or symptoms. In India, the rate of self-medication practices is rising exponentially as it is the cheapest way of treatment. But improper self-diagnosis and improper use of drugs is major part of concern these days. The wrong usage of medications is creating medication hazards, drug toxicities, drug interactions drug-food interactions etc. Methodology and Results: The present study enrolled total of 500 people (250 urban and 250 rural), of which, the age group of 36-45 consumed more self- medication both in urban (29.5%) and rural (24.40%) population. The illiterate (64.56%) people practiced more self- medication in rural areas where as in urban graduates (33.87%) practiced more self-medications. lower middle class (49.60%) people practiced higher self-medication in rural and upper class (67.21%) people practiced higher self-medication in urban. Analgesics and antipyretics drugs were most frequently used drugs in both urban and rural areas. Thereafter the self - medication population was divided into test and control group. The test group was given both pills and counselling whereas control group was given only pills, both groups were compared. After intervention, it was found that 30.50% self-medication dropped in urban test group, and 10.00% in the urban control group. In rural test group 36.00% of drop was observed in self-medication practices whereas in rural control group it was only 9.60%. Conclusion: Counselling played important role in reduction of self-medication practices in both urban and rural areas.
Keywords: Self-medication; Urban population; Rural Population; Medication hazards; India